PENGARUH KUALITAS LABA DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR BARANG KONSUMEN PRIMER - Fia Fadia Inayah; Ela Widasari; Siti Mudawanah (Universitas La Tansa Mashiro, 2023)
The value of the company becomes the main goal of the company because the value of the company is one of the indicators of the prosperity of the company or shareholders. The purpose of this study is to determine the Quality of Profit (KL), Return On Assets (ROA) and Earning Per Share (EPS) to Company Value proxied by Price Book Value (PBV) in Primary Consumer Goods Sector Companies listed on the Indonesia Stock Exchange (IDX) for the 2017 – 2021 period. This research method is causal quantitative with a research population of 103 companies, sampling techniques using purposive sampling techniques, so that a sample of 31 companies was obtained. To test the hypothesis, this study used multiple linear regression analysis techniques using IBM SPSS 25 software. The results of this study show that partially the quality of profit (KL) does not have a significant effect on price book value (PBV), partially return on assets (ROA) has a significant effect to Price Book Value (PBV), partially Earning Per Share (EPS) has a negative and significant effect on Price Book Value (PBV) and Simultaneously The Quality of Profit (KL), Return On Assets (ROA) and Earning Per Share (EPS) has a significant effect on the Price Book Value (PBV) in Primary Consumer Goods Sector Companies listed on the Indonesia Stock Exchange for the 2017-2021 period.